The Effect of Perceived Changes in Budget Allocations on Employee Motivation and Performance: Case Study on a Deputy of an Indonesian Coordinating Ministry - Meutia, Farah; Suharko, Arief (Journal of Entrepreneurship, Management and Industry (JEMI), 2022)
This study aims to determine whether the perception of changes in budget allocations has an effect on employee motivation and performance at one of the Deputy in the Coordinating Ministry using quantitative and qualitative methods. The magnitude of the perceived influence of changes in budget allocation as an independent variable will be assessed using Structural Equation Modeling (SEM) analysis using Partial Least Square (PLS) on each dependent variable, namely employee motivation and employee performance. In addition, it also assesses whether employee motivation can be a mediating variable. The data used were obtained from the results of questionnaires filled by 121 employees on the object of research. The SEM-PLS method in this study was used in validity testing, reliability testing, and hypothesis testing. The results of this analysis will be supported by descriptive narratives according to the results of observations on the object of research. The results of the study indicate that the perception of changes in budget allocations influences increasing employee motivation. However, the perception of changes in budget allocations has no effect on employee performance. Furthermore, the perception of changes in good budget allocations will improve employee performance if mediated by employee motivation.